ST09, A Novel Curcumin Derivative, Blocks Cell Migration by Inhibiting Matrix Metalloproteases in Breast Cancer Cells and Inhibits Tumor Progression in EAC Mouse Tumor Models - Snehal Nirgude; Raghunandan Mahadeva; Jinsha Koroth; Sujeet Kumar; Kothanahally S. Sharath Kumar; Vidya Gopalakrishnan; Subhas S Karki; Bibha Choudhary (Molecules, 2020)
Purpose: Curcumin is known for its anticancer and migrastatic activity in various cancers, including breast cancer. Newer curcumin derivatives are being explored to overcome limitations of curcumin like low bioavailability, stability, and side effects due to its higher dose. In this study, the synthesis of ST09, a novel curcumin derivative, and its antiproliferative, cytotoxic, and migrastatic properties have been explored both in vitro and in vivo. Methods: After ST09 synthesis, anticancer activity was studied by performing standard cytotoxicity assays namely, lactate dehydrogenase (LDH) release assay, 3-(4, 5-dimethylthiazol-2-yl)-2–5-diphenyletrazolium bromide (MTT), and trypan blue exclusion assay. Annexin-FITC, cell cycle analysis using flow cytometry, and Western blotting were performed to elucidate cell death mechanisms. The effect on the inhibition of cell migration was studied by transwell migration assay. An EAC (Ehrlich Ascites carcinoma) induced mouse tumor model was used to study the effect of ST09 on tumor regression. Drug toxicity was measured using aspartate aminotransferase (AST), alanine aminotransferase (ALT), blood urea nitrogen (BUN), and flow-cytometry based lymphocyte count. Histological analysis was performed for assessment of any tissue injury post ST09 treatment. Results: ST09 shows an approximate 100-fold higher potency than curcumin, its parent compound, on breast tumor cell lines MCF-7 and MDA-MB231. ST09 arrests the cell cycle in a cell type-specific manner and induces an intrinsic apoptotic pathway both in vitro and in vivo. ST09 inhibits migration by downregulating matrix metalloprotease 1,2 (MMP1,2) and Vimentin. In vivo, ST09 administration led to decreased tumor volume in a mouse allograft model by boosting immunity with no significant drug toxicity. Conclusion: ST09 exhibits antiproliferative and cytotoxic activity at nanomolar concentrations. It induces cell death by activation of the intrinsic pathway of apoptosis both in vitro and in vivo. It also inhibits migration and invasion. This study provides evidence that ST09 can potentially be developed as a novel antitumor drug candidate for highly metastatic and aggressive breast cancer.